Accuracy of Orthognathic Surgical Planning using Three-dimensional Virtual Techniques compared with Conventional Two-dimensional Techniques: a Systematic Review - Thomas Starch-Jensen; Federico Hernández-Alfaro; Özlem Kesmez; Romario Gorgis; Adaia Valls-Ontañón (eJournal of Oral Maxillofacial Research)
Objectives: The objective was to assess the accuracy of orthognathic surgical planning using three-dimensional virtual planning compared with conventional two-dimensional planning.